2016
DOI: 10.1136/bcr-2015-213085
|View full text |Cite
|
Sign up to set email alerts
|

Is constipation a trivial matter?

Abstract: Constipation is a common symptom of patients presenting to the emergency department. If poorly managed, it can have significant consequences. A 50-year-old man was admitted to the emergency department following cardiac arrest. His medical history included a diagnosis of cerebral palsy and multiple admissions to hospital with constipation. Clinical examination revealed a grossly distended and tense abdomen. Circulatory supply to the lower limbs was acutely impaired. CT scan revealed massive dilation of the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…He presented to the emergency department in a state of cardiac arrest. The patient eventually demised and this was retrospectively attributed to abdominal compartment syndrome from severe constipation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…He presented to the emergency department in a state of cardiac arrest. The patient eventually demised and this was retrospectively attributed to abdominal compartment syndrome from severe constipation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s presentation was caused by severe constipation. Our literature review identified one case of ACS in an adult caused by constipation likely secondary to neurogenic bowel 8 and two cases thought to be due to clozapine use. 9 Her longstanding constipation was likely due to her medication regimen of clozapine, risperidone, and the anticholinergic medications glycopyrrolate and benztropine.…”
Section: Discussionmentioning
confidence: 99%